PENGARUH KEBIASAAN KONSUMSI ENERGI, PROTEIN, DAN SENG TERHADAP KEJADIAN STUNTING PADA ANAK USIA SEKOLAH DASAR DI KECAMATAN SALAPIAN KABUPATEN LANGKAT TAHUN 2017 - Rismeni Saragih (Jurnal Riset Hesti Medan, 2017)
Stunting is one form of nutritional abnormalities in terms of body size characterized by a short body condition to exceed the -2SD deficit below the WHO standard. This study aims to determine the effect of consumption habits of energy sources, protein, and zinc to the incidence of stunting in school-aged children in Tanjung Langkat Village Kecamatan Salapian Kabupaten Langkat. This research is an observational analytic research with case control design. The number of research samples were 29 cases and 29 controls selected using stratified random sampling method. Data of energy consumption habits, protein, and zinc was done by interview using 24 hour food recall form and form food frequency and stunting data obtained from measurement of body height by using microtoise which processed by using Software WHO Anthroplus. Data analysis was done by univariante analysis, bivariate analysis, and multivariate analysis by using chi-square test and logistic regression test. The result of the analysis showed that there were three variables that had significant relation on the stunting event, energy consumption habits (p=0.036; OR=3.109), protein consumption habits (p=0.035; OR=3.148) and zinc consumption habits (p=0.002; OR=5,971). The most dominant factor influencing the stunting event is the consumption habit of zinc source with Exp. (B)=5.737. It is advisable to improve the provision of information and understanding to children and parents about the importance of consuming food sources of energy, protein, and zinc as well as expected to parents to pay attention and familiarize children consuming diverse types of food and suggested to the school to cooperate with puskesmas provide counseling related to the consumption of balanced nutritious foods, especially those that play a role in the growth of children.